TANTANGAN PENERAPAN HUKUM KEWARISAN ISLAM DALAM MASYARAKAT BUGIS - Sapriadi, Sapriadi; Darliana, Darliana; Sylviah, Sylviah; Rahma Syam, Anna (Jurnal AL-SYAKHSHIYYAH Jurnal Hukum Keluarga Islam dan Kemanusiaan, 2025)
This article examines the urgency of implementing Islamic inheritance law in Indonesia, which emphasizes justice and public welfare for heirs. Although it has been recognized within the national legal system, its implementation still faces significant challenges. Conflicts among heirs frequently arise due to differing understandings, interests, and limited public knowledge of Islamic inheritance principles and distribution mechanisms. Inadequate education and socialization weaken legal awareness, while varying interpretations among Islamic schools of thought and scholars increase complexity and dispute potential. This article analyzes the root causes of these challenges and proposes strategic solutions, including strengthening public education, simplifying legal procedures, and enhancing the role of relevant institutions in resolving inheritance disputes. The study aims to promote a more just, transparent, and Islamic justice-oriented inheritance system.